From bricks-and-mortar to bricks-and-clicks: logistics networks in omni-channel grocery retailing - Wollenburg, Johannes; Hübner, Alexander; Kuhn, Heinrich; Trautrims, Alexander (Emerald Publishing, 2018)
Purpose: The advent of grocery sales through online channels necessitates that bricks-and-mortar retailers redefine their logistics networks if they want to compete online. Because the general understanding of such bricks-and-clicks logistics systems for grocery is still limited, the purpose of this paper is to analyze the internal logistics networks used to serve customers across channels by means of an exploratory study with retailers from different contexts. Design/methodology/approach: A total of twelve case companies from six European countries participated in this exploratory study. Face-to-face interviews with managers were the primary source for data collection. The heterogeneity of our sample enabled us to build a common understanding of logistics networks in grocery retailing on multiple channels and to understand the advantages of different warehousing, picking, internal transportation and last-mile delivery systems. Findings: Bricks-and-mortar grocery retailers are leveraging their existing logistics structures to fulfill online orders. Logistics networks are mostly determined by the question of where to split case packs into customer units. In non-food logistics channel integration is mostly seen as beneficial, but in grocery retailing this depends heavily on product, market and retailer specifics. The data from our heterogeneous sample reveals six distinct types for cross-channel order fulfillment. Practical implications: Our qualitative analysis of different design options can serve as decision support for retailers developing logistics networks to serve customers across channels. Originality/value: The paper shows the internal and external factors that drive the decisionmaking for omni-channel logistics networks for previously store-based grocery retailers. Thereby it makes a step towards building a contingency and configuration theory of retail networks design. It discusses in particular the differences between grocery and non-food omni-channel retailing, lastmile delivery systems and market characteristics in the decision-making of retail networks design.